ANXIETY REDUCES SEXUAL ACTIVITY AMONG ELDERLY WOMAN IN BLAHBATUH GIANYAR - Martini, Ni Made Dwi Ayu (E-Jurnal Medika Udayana; Vol 10 No 9 (2021): Vol 10 No 09(2021): E-Jurnal Medika Udayana, 2021)
Sexual activity is one of the basic human needs that must be met, but changes due to the aging process can affect sexual activity. These include anxiety and menopause, which can cause fear or worry in certain situations. This study was conduct to determine the relationship between anxiety and sexual activity among elderly women in Blahbatuh, Gianyar. This research is a cross-sectional quantitative study with a total sample of 29 people using incidental sampling techniques. Data were collected using a questionnaire and analyzed using the Spearman Rank test. The results of the study were 75.9% of respondents experienced moderate anxiety, 73.3% of respondents were in the category of not sexually active, and there is a relationship between anxiety and sexual activity among elderly women in Blahbatuh, Gianyar (p = 0.001). The elderly are expected to be able to overcome their anxiety in order to increase their sexual activities.